ESTUDO DA ELETRO-OXIDAÇÃO DE ETANOL SOBRE CATALISADORES de Pt/C, PtIr/C, PtW/C, PtSn/C e PtIrSn/C PREPARADOS PELO MÉTODO DE REDUÇÃO POR ÁLCOOL - Granja, Deracilde Santana da Silva (2013)
Electrocatalyst containing platinum supported on high surface area carbon Vulcan XC-72 were synthesized by the method of reduction by alcohol and tested in comparation of ethanol oxidation in acidic medium. The materials studied were Pt/C, Pt80Ir20/C, Pt80W20/C, Pt80Sn20/C and Pt60Ir10Sn30/C, using as a standard for comparison the commercial catalyst Pt/C 20% E-TEK. Physical characterization was performed using techniques Energy dispersive X-ray (EDX), X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM) and scanning electron microscopy for high-resolution field emission ("Field emission electron gun ") (SEM- FEG). The EDX analysis showed that the compositions theoretical synthesis are very close to the experimental values. From the results obtained by X-ray diffraction it was possible to calculate the average crystallite size and lattice parameter of the samples. All materials showed a crystalline structure characteristic of face centered cubic structure with platinum modifications of the lattice parameter as a function of added metal. Analysis of TEM and SEM-FEG provided the particle size and the distribution and dispersion in the carbon support. The results compared to electrochemical oxidation reaction of ethanol showed that the addition of different metals to platinum increased the catalytic activity of the electrodes and among the ternary materials studied showed best response under the conditions studied.